Batiteria: The Epistemology of Contemporary Musical Creation Based on the Aceh Spice Route - Rizki Mona Dwi Putra; Uswatul Hakim; Vereki Martiano (Gondang: Jurnal Seni dan Budaya, 2026)
This article examines the epistemological foundations underlying the creation of the contemporary musical work Batiteria—a work born from research on the Acehnese spice route as a cultural phenomenon. This study uses an artistic research approach that positions artworks as both products and vehicles for reflection on knowledge. By integrating three epistemological axes—(1) practice-based knowledge, (2) an epistemology of reinterpretation that explores how artists “know” traditions before transforming them, and (3) a multi-source epistemology that combines empirical, intuitive, and cultural knowledge—this study analyzes how Batiteria constructs new musical knowledge. Batiteria, an acronym for West, East, and Central Aceh Rhythms, interprets three traditional Acehnese rhythms: Rapai Geleng (West Aceh), Rapai Pasee (East Aceh), and Didong (Central Aceh) through techniques of musical reinterpretation and contemporary composition. The findings indicate that the creation process of Batiteria is not merely expressive, but rather an epistemic act that produces knowledge about tradition, identity, and cultural sustainability through the language of sound. Thus, this article contributes to the development of discourse on the epistemology of art—particularly in the context of tradition-based contemporary music creation in Indonesia.